Gestão de centro de pesquisa universitária em project studies: barreiras e facilitadores - Batista, Marcio Rogerio (2024)
Academic institutions face growing pressure to demonstrate tangible results and generate significant impacts in a context of rapid transformations and demands for innovation. In this landscape, University Research Centers (URCs) play a leading role by integrating research, teaching, and social impact, establishing themselves as hubs of interdisciplinary innovation. However, the management of these URCs presents complex challenges, such as balancing scientific excellence with practical relevance, which requires adaptive approaches to ensure their sustainability. This study aimed to explore the barriers and facilitators in URC management, focusing on the context of Project Studies, which combines theory and practice to solve complex problems and foster innovation. The general objective was to synthesize the barriers and facilitators present in the management of URCs in Project Studies, using Contingency Theory as the theoretical framework to understand how different contextual factors, such as internal and external environment, structure, and technology, influence the management of these centers. From this, the following specific objectives were defined: (a) to describe the institutional objectives guiding the management of URCs in Project Studies; (b) to identify and categorize the barriers and facilitators in URC management within Project Studies; (c) to map the impacts and respective practices adopted by URCs in Project Studies to manage barriers and facilitators; (d) to understand the interactions between barriers and facilitators in light of Contingency Theory; and (e) to propose strategies to mitigate barriers and enhance facilitators, contributing to the sustainability of these centers. The research was conducted in two stages. In the first stage, a Systematic Literature Review (SLR) was carried out, consolidating the theoretical base on barriers and facilitators in URC management and identifying gaps and opportunities for further investigation. In the second stage, a multiple-case study allowed for a comparative analysis of different contexts, providing a comprehensive view of the challenges and opportunities. Contingency Theory guided the analysis by identifying how barriers and facilitators may vary according to specific contextual factors, such as institutional resources, organizational structure, external policies, and stakeholder demands. Primary data collection was carried out through 28 semi-structured interviews with URC managers and researchers, complemented by documentary analysis, ensuring a deep and contextualized understanding of the phenomena under investigation. The results revealed barriers, facilitators, and their impacts, as well as the strategies used by URCs to address these factors. As a contribution, a framework was developed that synthesizes these interactions and offers practical support for URC management, considering the influence of contingent variables. Future research is recommended to expand the analysis to other contexts and explore the interrelationship between barriers and facilitators at different institutional levels, contributing to a broader understanding of the contingencies affecting URC management.